If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2k + -6k = 3(7 + -2k) + -7(8k + 3) Combine like terms: 2k + -6k = -4k -4k = 3(7 + -2k) + -7(8k + 3) -4k = (7 * 3 + -2k * 3) + -7(8k + 3) -4k = (21 + -6k) + -7(8k + 3) Reorder the terms: -4k = 21 + -6k + -7(3 + 8k) -4k = 21 + -6k + (3 * -7 + 8k * -7) -4k = 21 + -6k + (-21 + -56k) Reorder the terms: -4k = 21 + -21 + -6k + -56k Combine like terms: 21 + -21 = 0 -4k = 0 + -6k + -56k -4k = -6k + -56k Combine like terms: -6k + -56k = -62k -4k = -62k Solving -4k = -62k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '62k' to each side of the equation. -4k + 62k = -62k + 62k Combine like terms: -4k + 62k = 58k 58k = -62k + 62k Combine like terms: -62k + 62k = 0 58k = 0 Divide each side by '58'. k = 0 Simplifying k = 0
| 4.5b-5.25b+3=3.75 | | (x^2-2x-2)(x^2-12x+37)=0 | | y=9.5(20)+100 | | 12x=46-6x | | 50-3x=15+2x | | 4.5+5.25+3=3.75 | | 4x+17=-2x+3 | | 2x^2-14=-64 | | 3x-5=6x-5 | | 92-20=9h | | y=9.5x+100 | | n+0.5=-2.833 | | 4.5b-5025b+3=3075 | | 15=-6+4(d+3) | | -16-t=7 | | (3-2x)=7 | | 6+6x-10=-20 | | 6x-10x=10x-10x-2 | | -17r+8=42 | | -4(3x+3)=7x-2 | | 2y=-172-6x | | -4h+8=36 | | 3(2x+3)=4(x-6) | | 2-.33x=26 | | 18(6m+7)=-9(8m+6) | | 8s+16=4 | | .5x+6=18 | | -10.25y=-9.33 | | 2y=172-6x | | 6d+3d+6d+7-5d=0 | | 14x-7x=7x-7x-21 | | 36-6n=5(1+5n) |